Moderating effects of general self-efficacy on courtesy stigma and anxiety and depressive symptoms of parents of children with autism spectrum disorder - Tong, Jiao; Chen, Xu; Wang, Bin; Wang, Tao; Wang, Xue; Ma, Shan; Shi, Dongdong; Wang, Xin; Yan, Dongmei (Frontiers in Psychiatry, 2024)
Background Stigma, anxiety and depressive symptoms are highly prevalent in parents of children with autism spectrum disorder (ASD) and may have a detrimental impact on the rehabilitation and treatment of children with ASD, ultimately leading to more behavioral issues and higher rates of disability. Therefore, the purpose of this study was to identify the association between general self-efficacy, courtesy stigma, and anxiety and depressive symptoms, and to further discuss whether general self-efficacy moderated the association between courtesy stigma and anxiety and depressive symptoms in parents of children with ASD. Methods A total of 409 parents of children with ASD from Lianyungang, Jiangsu Province, Eastern China participated in a cross-sectional survey. A structured questionnaire was used to collect sociodemographic characteristics, courtesy stigma, general self-efficacy, anxiety symptoms, and depressive symptoms. Hierarchical multiple regression was used to assess the associations of courtesy stigma, general self-efficacy and courtesy stigma × general self-efficacy interaction with anxiety and depressive symptoms. Simple slope analysis was used to visualize the interaction. Results The courtesy stigma of parents of children with ASD was positively correlated with anxiety (B = 0.374, P < 0.001) and depressive symptoms (B = 0.366, P < 0.001). General self-efficacy was negatively correlated with anxiety (B = -0.200, P < 0.001) and depressive symptoms (B = -0.210, P < 0.001). The association between courtesy stigma and anxiety symptoms was different in the high (1 standard deviation (SD) above the mean, b = 0.258, standard error (SE) = 0.056, t = 4.567, P < 0.001) and low (1 SD below the mean, b = 0.470, SE = 0.053, t = 8.870, P < 0.001) groups of general self-efficacy. In addition, the association between courtesy stigma and depressive symptoms was also different in the high (1 SD above the mean, b = 0.241, SE = 0.056, t = 4.268, P < 0.001) and low (1 SD below the mean, b = 0.469, SE = 0.053, t = 8.844, P < 0.001) groups of general self-efficacy. Conclusions General self-efficacy could moderate the impact of courtesy stigma on anxiety and depressive symptoms. Therefore, among parents of children with ASD who experienced high courtesy stigma, enhancing general self-efficacy could be an effective strategy to reduce anxiety and depressive symptoms in this population.